The Effectiveness of Online Couple Class towards the Increase of Husband Support and the Increase of Haemoglobin Rate of Pregnant Women during the Pandemic - Ayesha Hendriana Ngestiningrum; Nurwening Tyas Wisnu; Nuryani Nuryani; Teta Puji Rahayu; Ruli Agustina (Health Notions, 2021)
Iron deficiency anemia that often occurs in pregnancies may be due to the pregnant women’s inconsistency in consuming Fe tablets. The husbands’ role is required to increase their consumption. This research aims to analyze the effectiveness of online couple classes in increasing the husbands’ support and in increasing the Hb Rate of pregnant women with anemia. This is quasi-experiment research, with a pretest-posttest one-group design. This research is located at the Kartoharjo Community Health Center Area, Magetan Regency, East Java, Indonesia, in 2020. The sample of this research is 18 pregnant women with anemia (Hb